Pemanfaatan Kulit Buah Naga Merah Sebagai Bahan Baku Pembuatan Glukosa Cair dengan Proses Hidrolisis Enzimatis - Awildan El Fath; Naufal Alkautsar Maulana; Rachmad Ramadhan Yogaswara (G-Tech: Jurnal Teknologi Terapan, 2024)
Red dragon fruit skin contains many beneficial nutrients. The carbohydrate composition of dragon fruit skin includes 11.5% of the whole, with details of lignin 37.18%, cellulose 9.25%, starch 11.07%, pectin 10.79%. This study aims to understand the effect of enzyme concentration used, namely α-amylase and β-amylase enzymes and also the effect of hydrolysis time, on the glucose content produced. The method used is a hydrolysis method that utilizes enzymes, namely the enzymatic hydrolysis method. The variables determined were the concentration of enzymes used and the length of time the hydrolysis was carried out. The process was carried out by mixing the solution with α-amylase and β-amylase enzymes into a glass beaker using various enzyme variations and hydrolysis times. Both variables were run in a waterbath at 65℃ and the pH of the solution was pH 5-6. The best condition was obtained at (1%:5%) α-amylase and β-amylase concentratiom  and 5 days of hydrolysis time with 62.2% glucose content, 37.15% water content and 0.25% ash content.